Model Pembelajaran PAUD Inklusi (Studi Kasus Lembaga PAUD ECCD-RC Yogyakarta) - Abdul Latif, Muhammad; 'Aziz, Hafidh (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
Aims of this study was to examine the learning model of PAUD Inclusion in a case study at Lembaga PAUD ECCD-RC Yogyakarta. The method used is qualitative research with a phenomenological approach. Data collection techniques using passive participation observation, semi-structured interviews and documentation. Data analysis using the Milles Huberman model with data validity testing in the form of triangulation of techniques and sources. The results of this study indicate that the model applied in Lembaga PAUD ECCD-RC Yogyakarta is learning area by dividing areas within the classroom and areas outside the classroom. The learning process in the area is in accordance with the theory of learning in the area that is involved in the initial activities, core activities, breaks and closing activities. Factors that support learning are special facilitators, adequate library facilities and a conducive school environment. The inhibiting factors consist of facilities that not all PAUD graduates and special child service facilities are lacking